ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ðµ ÑÐ´Ñ€Ð¾ÑÐ¾Ð´ÐµÑ€Ð¶Ð°Ñ‰Ð¸Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ Ð¿Ð¾Ð´ Ð·Ð°Ñ‰Ð¸Ñ‚Ð¾Ð¹ Ð½ÐµÐ¿Ñ€Ð¾Ð½Ð¸ÐºÐ°ÑŽÑ‰ÐµÐ³Ð¾ ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð° ÐŸÐÐž-1500 - Babijchuk, Lyubov A.; Mykhailova, Olga A.; Ryazantsev, Vladimir V.; Zubov, Pavel M.; Migunova, Regina K. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2016)
Development of wash-free cryopreservation methods for cord blood nucleated cell fraction, including the population of hematopoietic stem/progenitor cells, is an actual task for their long-term storage. Present investigation involved the technique of cord blood nucleated cells cryopreservation, comprising the isolation of cell population by the original two-step centrifugation method, the treatment with non-penetrating cryoprotectant polyethylene oxide with molecular weight of 1500 (PEO-1500) and freezing by the two-step program. This technique enabled to preserve more than 72% CD45+ and 75% CD34+ cells with the viability indices of correspondingly 83 and 91% and higher. Herewith, an increased content of reactive oxygen species (42.7 Â± 6.3%) on the background of high cell number and their viability may be considered as a cellsâ€™ physiological response to the effect of cryopreservation factors.Probl Cryobiol Cryomed 2016; 26(1):24-34.